PENGARUH PENGGUNAAN STRATEGI LARI KANAN KIRI BENAR SALAH TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN BAHASA INGGRIS KELAS IV DI MIN PEMURUS DALAM BANJARMASIN - Jannah, Raihanatul; Salmah, Syarifah; Yahya, Barkah Alida (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2017)
Left-right run and true-false strategy is the activity hearing a true statement then run to the right and when hearing a false statement then run to the left. The learning outcome is the ability the student receives after learning activities. The english language learning was about my body's material for IV grade. This research aims to know the result of student learning by using Left-right run and true-false strategy on learning English and to know if there is a significant influence to student learning outcome by using Left-right run and true-false strategy. This research is field research by using experimental method. The sample in this research is the fourth graders of MIN Managers in Banjarmasin. IV grade students A are as experimental classes (using Left-right run and true-false strategy) and fourth-grade students B are as control class (using index card match strategy). The material taught is my body material. The result of the research shows that the use of Left-right run and true-false strategy can improve the students' learning outcomes in fourth grade English learning at MIN Pemurus Dalam in Banjarmasin. It is based on the analysis of student learning outcomes of experimental and control class. Experimental results of experimental class students are better than the results of the control class students. This can be seen from the average value of the experimental group students at 87.82 whereas the average grade of the control class students is 64.09. Based on average posttest results, the difference is 23.73. Left-right run and true-false strategy has a significant effect on student learning outcomes in fourth grade English learning at MIN Pemurus Dalam in Banjarmasin. This is based on a different test that states Ho is rejected and Ha is accepted.